Vladislav Shutochkin. Turkish vector of international activities of Ukrainian universities in the XXI century. - Shutochkin, Vladislav (Young Scholars Grinchenko – Seton International Journal, 2021)
Vladislav Shutochkin. Turkish vector of international activities of Ukrainian universities in the XXI century. Abstract. The article provides a comprehensive analysis of the cooperation of Ukrainian universities with Turkish Republic, which has developed in the XXI century. First of all, the history of the formation of relations, which became the basis for the establishment of modern educational cooperation, is shown. Prospects for further development of contacts between the states are also indicated. The content of cooperation is revealed on the basis of the analysis of reports of Ukrainian universities, scientists and certificates of the diplomatic mission of Ukraine in Turkey. The forms and directions of relations are shown, which have developed between higher educational institutions of Ukraine with Turkey in the XXI century. The issue of educational cooperation between Ukraine and Turkey has been partially considered by domestic scholars, so it deserves detailed and comprehensive consideration. Since gaining independence in 1991, Ukraine has sought to meet current trends in advanced educational standards. Educational cooperation allows Ukraine to learn from experience and transform its own education system. Ukraine already cooperates with many European countries, such as Poland, Lithuania, Germany, Great Britain and the Czech Republic. At the same time, Ukraine is developing cooperation with Asian countries. One of such countries is Turkish Republic, which has significant international influence in the world and is an important economic and geopolitical partner for Ukraine. Leading universities of Ukraine sign cooperation agreements and organize joint conferences with the Turkish side. Countries also implement academic mobility programs among students. Thanks to educational cooperation between the states, Ukraine increases its international prestige in the geopolitical and socio-cultural space. In general, partnerships contribute to the cultural enrichment of both countries. We hope that the educational contacts between Ukraine and Turkey will continue to strengthen, and that the Republic of Turkey will remain a successful partner of Ukraine in the field of education and science. Keywords: Ukrainian-Turkish relations, educational cooperation, cultural relations, university.